Peningkatan Kualitas Layanan Wisata Taman Impian Jaya Ancol untuk Memaksimalkan Kepuasan Pengunjung - Puji Erlina; Fidella Damayanti; Fachrizal Satrio Putro Yuwono (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Analyze the impact of service quality on visitor satisfaction at Taman Impian Jaya Ancol. Using a qualitative method, the research identifies service quality dimensions based on the SERVQUAL model, including reliability, responsiveness, assurance, empathy, and tangibles. The findings reveal that the Tangible dimension contributes the most to visitor satisfaction, while Responsiveness needs improvement. Additionally, the study highlights that technological innovations, such as digital payment systems and tourism apps, enhance visitor experiences. These findings underscore the importance of technology-driven service development in improving customer satisfaction, loyalty, and competitiveness in the tourism industry.